A Study of Innovations in Higher Education Marketing for Admissions and Its Impact on Students’ Behavior (Trinity Journal of Management, IT & Media (TJMITM), 2015)
Higher education as a part of service sector plays an important role  in the development and growth of a country. India is no excep tion to this. In fact service sector contributes to the 54% highest to  the GDP. In current scenario, a customer satisfaction and service  quality are considered the fundamental marketing framework to  determine the loyalty. Higher education is a pure service and is  characterized by a greater amount of interpersonal contact, com plexity, divergence, and customization than other service business es. In order to create an effective admission plan it is crucial to  know the factors that influence the students’ decision making pro cess and to understand the nature of the relationship among these  factors. The potential students generally get influenced by family  members, senior students, fellow classmates, senior citizens & fac ulty references. Amidst all this they also get influenced by college  advertisement through various media. A student takes into many  factors before deciding admission into an institute. But it has to be  debated how far marketing of higher education by some private  colleges / universities would lead to admissions. It is quite inter esting to know the role played by various stakeholders such as par ents, teachers, friends, classmates into the final admission decision  making process. It appears that a student will play a major role in  the final admission decision. Now a day’s lots of innovations are  taking place to make targeted candidates to become students I that  college/university for which marketing /promotions made.
Keywords: Innovations; Higher Education Marketing; Students’ Behavior; GDP; (HEIs)